17ß-oestradiol (1 mg) plus drospirenone (2 mg) in hormonal therapy of postmenopausal period - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Low-dose oral MHT combining 1 mg oestradiol (E2) and 2 mg drospirenone (DRSP) is effective in alleviating climacteric and urogenital symptoms, prevents endometrial hyperplasia, reduces the risk of osteoporosis, and has a positive influence on lipid profile, carbohydrate metabolism, arterial pressure and female quality of life. This safe type of MHT can be a drug of first choice for the big group of women after menopause.